Experimental analysis of small solar ummanned aerial vehicle to predict aerodynamic performance - Rajendran, Parvathy; Smith, Howard (National Institute for Aerospace Research - INCAS, 2020)
Various studies have been done in recent years on unmanned solar-powered aircraft for non-stop flight at a specified location or area. However, if a solar-powered unmanned aerial vehicle (UAV)can achieve a non-stop flight around the world, it may lead to the possibility of a pseudolite (i.e., pseudo-satellite) operation. These solar UAVs capable of operating as a satellite enable sustainable aviationthat provides cheaper communication accessibility. Recently, we have developed a mathematical model for solar UAVs that was followed by the fabrication of a solar UAV model. Both the mathematical design model and the prototype model have been published. Thus, this work aims to determine the actual flight performance characteristics of the fabricated solar UAV. In this work, the bench and flight tests of the prototype solar and non-solar UAV model were compared in terms of aerodynamic characteristics and performance. These characteristics are determined using the flight test data and then compared with simulation data using a mathematical design model published earlier. Both accelerated and un-accelerated methods have been applied to predict the polar drag curve, and a distinct band of data obtained for both UAV prototypes. The predicted zero-lift drag coefficients were similar to the theoretical prediction in these UAVs
Keywords: accelerated method; drag polar; flight test; UAS; UAV; drone; solar-powered UAV; SUAV design